2014
DOI: 10.3402/gha.v7.25856
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward universal health coverage in ASEAN

Abstract: BackgroundThe Association of Southeast Asian Nations (ASEAN) is characterized by much diversity in terms of geography, society, economic development, and health outcomes. The health systems as well as healthcare structure and provisions vary considerably. Consequently, the progress toward Universal Health Coverage (UHC) in these countries also varies. This paper aims to describe the progress toward UHC in the ASEAN countries and discuss how regional integration could influence UHC.DesignData reported in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 16 publications
0
77
0
1
Order By: Relevance
“…The same studies have identified economic crisis and the inflation as the main causes of socioeconomic problems [61,79]. Countries can ease the work of achieving UHC by mitigating the consequences of the economic crisis [119], concentrating on achieving economic growth [61,138,161], and by increasing the GDP share of THE [121,141].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same studies have identified economic crisis and the inflation as the main causes of socioeconomic problems [61,79]. Countries can ease the work of achieving UHC by mitigating the consequences of the economic crisis [119], concentrating on achieving economic growth [61,138,161], and by increasing the GDP share of THE [121,141].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving UHC requires a powerful and multilateral support at the very top of the country's political system. The political and national commitment to support the healthcare system is a major influencing factor in implementing programs of UHC [51,124,141,155].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a clear example of the 'fragile labour of welcoming' (Darling 2018, 224), after the Health Minister proclaimed in 2014 that foreigners were 'eating up our [Malaysian citizens'] medical subsidy' (Zuhrin 2014) foreigners were required to cover the real cost of their treatment at public health facilities, resulting in an exponential increase in medical costs for them. For example, a consultation with a public medical specialist costing citizens MYR5 (US$1) would cost migrants MYR60 (US$14) (Van Minh et al 2014). 2 In April 2017, the Ministry of Health announced a sharp increase in deposits for migrants seeking treatment at public hospitals, raising these by 130-230% (The Malay Mail Online 2017).…”
Section: Hierarchies Of Health Care In An Entrepreneurial Statementioning
confidence: 99%
“…Ensuring an adequate workforce to meet the health needs of the population is just the first step in ensuring health equity for the population. Malaysia, Singapore, and Thailand all offer universal health coverage with other ASEAN countries at varying stages of advancement toward universal health coverage (Van Minh et al, ). By using the resources at hand, such as the MRA on nursing services, a common goal to improve nursing throughout the region, and the desire to present a strong united economy through the ASEAN Economic Community, nurses can both address the recognized need of nursing services and promote health equity for the betterment of society.…”
Section: The Futurementioning
confidence: 99%